Fertilizer Requirements of Newly Planted Teak (Tectona grandis L.f.) Seedlings - Abod, Sheikh Ali; Siddiqui, Muhammad Tahir (Universiti Putra Malaysia Press, 2001)
The results of the present study indicated that height and diameter increments of newly planted teak seedlings were significantly affected by N and P fertilizers. Leaf weight, shoot weight, root weight and total dry matter production showed statistically significant responses to fertilizer application at harvest, one year after planting. Root-shoot ratio decreased as a result of fertilizer application. The present study also revealed that the application of 300 kg/ha triple superphosphate and 200 kg/ha ammonium sulphate are required to enhance the height and diameter growth and total plant weight of newly planted teak seedlings on Penambang soil series.